2017
DOI: 10.1111/aogs.13133
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian reserve after salpingectomy: a systematic review and meta‐analysis

Abstract: Introduction. Although there has been a growing concern over the possible damaging effect of salpingectomy on ovarian reserve, this issue remains uncertain. The purpose of this meta-analysis was to test the hypothesis that salpingectomy may compromise ovarian reserve. Material and methods. A detailed search was conducted using MEDLINE, Embase, Dynamed Plus, ScienceDirect, TRIP database and the Cochrane Library from January 2000 to November 2016. All cohort, cross-sectional and randomized controlled studies inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 30 publications
0
35
0
1
Order By: Relevance
“…92,93 Such efforts may be cost-effective and acceptable alternatives for women unwilling to undergo risk-reducing bilateral salpingo-oophorectomy. 92,94,95 A recent meta-analysis has indicated that salpingectomy does not impact ovarian reserve in the short-term, 96 however longer-term effects remain unclear and need to be assessed. Radical removal of the fimbrial end of the tube as a way to reduce risk in these women is being trialed in a study in France, 97 while in the United States, a clinical trial of bilateral salpingectomy with delayed oophorectomy in BRCA mutation carriers is currently underway.…”
Section: Risk-reducing Salpingectomy and Delayed Oophorectomy In Womementioning
confidence: 99%
“…92,93 Such efforts may be cost-effective and acceptable alternatives for women unwilling to undergo risk-reducing bilateral salpingo-oophorectomy. 92,94,95 A recent meta-analysis has indicated that salpingectomy does not impact ovarian reserve in the short-term, 96 however longer-term effects remain unclear and need to be assessed. Radical removal of the fimbrial end of the tube as a way to reduce risk in these women is being trialed in a study in France, 97 while in the United States, a clinical trial of bilateral salpingectomy with delayed oophorectomy in BRCA mutation carriers is currently underway.…”
Section: Risk-reducing Salpingectomy and Delayed Oophorectomy In Womementioning
confidence: 99%
“…A systematic review and meta‐analysis of six longitudinal studies and two cross‐sectional studies was published in 2017 . Either meta‐analysis comparing pre‐ and postoperative serum AMH or comparing the salpingectomy and control groups showed no significant differences in serum AMH levels.…”
Section: Gynecological Diseases and Interventionmentioning
confidence: 99%
“…Our survey demonstrated that 33.5% of respondents still worried about UAE leading to POI, especially in tertiary hospitals where UAE procedures are completed more frequently. BS and BTL are less likely to induce POI, as they may have no short-term signi cant effects on ovarian function indicators [44][45][46]. However, their long-term effect on fertility outcomes remains uncertain [44,47].…”
Section: Surgeries or Proceduresmentioning
confidence: 99%